O-76 First results from the action study. (1st September 2015) - Korfage, Ida J; Christensen, CA; Rietjens, Judith AC; Johnsen, AT; Groenvold, M; van der Heide, Agnes
Abstract : ACTION is a phase III multicenter cluster randomised controlled trial, in which 22 hospitals in Belgium, Denmark, Italy, the Netherlands, Slovenia, and the United Kingdom are randomised. In the intervention sites, patients are offered interviews with a trained facilitator, following the Respecting Choices ACP program. In the control sites, patients receive care as usual. In total, 1360 patients will be included. All participating patients will be asked to complete questionnaires at inclusion, and at 2.5 and 4.5 months post-inclusion. If a patient dies within a year after inclusion, a relative will be asked to complete a questionnaire on end-of-life care. Use of medical care will be assessed by checking medical files. Today we will present results of the feasibility study.